Multiple mirror aneurysms: Does the embryological perspective merit a special mention? - Maiti, TanmoyKumar; Konar, Subhas; Nanda, Anil (Neurology India, 2015)
During the preliminary imaging, multiple unruptured aneurysms were suspected and a formal four-vessel digital subtraction angiography revealed two pairs of mirror aneurysms involving the cavernous segment of ICA and MCA bifurcation [Figure 1]. Interestingly, one patient,[2] having the latter type of multiple mirror aneurysms, had multiple first-degree relatives with ruptured intracranial aneurysms.